Association of the ROBO1 gene with reading disabilities in a family‐based analysis. (20th March 2014) - Tran, C.; Wigg, K. G.; Zhang, K.; Cate‐Carter, T. D.; Kerr, E.; Field, L. L.; Kaplan, B. J.; Lovett, M. W.; Barr, C. L.
<x xml:space="preserve">Abstract</x> Linkage studies have identified a locus on chromosome 3 as reading disabilities (RD) and speech and sound disorder (SSD) susceptibility region, with both RD and SSD sharing similar phonological processing and phonological memory difficulties. One gene in this region, roundabout homolog 1 (ROBO1), has been indicated as a RD candidate and has shown significant association with measures of phonological memory in a population‐based sample. In this study, we conducted a family‐based association analysis using two independent samples collected in Toronto and Calgary, Canada. Using the two samples, we tested for association between ROBO1 single nucleotide polymorphisms (SNPs) and RD, along with quantitative measures for reading, spelling and phonological memory. One SNP, rs331142, which was selected based on its correlation with ROBO1 expression in brain tissue, was found to be significantly associated with RD in the Toronto sample with over transmission of the minor C allele (P = 0.001), correlated with low expression. This SNP is located ∼200 bp from a putative enhancer and results for a marker within the enhancer, rs12495133, showed evidence for association with the same allele in both the Toronto and Calgary samples (P = 0.005 and P = 0.007). These results support previous associations between ROBO1 and RD, as well as correlation with low gene expression, suggesting a possible mechanism of risk conferred by this gene.